Development of dental specialties in Iran: A qualitative study - Rojhanian, Tayebe; Jadidfard, Mohammad Pooyan; Yazdani, Shahram (Journal of Contemporary Medical Sciences, 2022)
Objectives: Dental specialties in Iran were first established in 1970s, and developed over time. Considering that information is essential for health policymaking, and lack of it is the main problem; therefore, policymakers require adequate knowledge about development and alterations of healthcare providers to recognize the influential factors on them. Regarding the information gap on development of dental specialties in Iran, this qualitative study aimed to assess it. Methods: This qualitative case study was conducted through 12 semi-structured interviews with the experts and pioneers of the oral healthcare system in Iran who were selected by purposive and snowball sampling. Data were analyzed by content analysis method, which included transcribing, identifying the meaning units, abstracting the content, sorting codes, and formulating themes using Atlas.ti software. Results: After data analysis, three main themes were extracted regarding development of dental specialties in Iran according to the interviewees: (A) trend of development, (B) challenges of development, and (C) necessities of development. Trend of development of dental specialties included two comprehensive phases, and one phase focusing on quantity and inadequate attention to quality. The challenges of development of dental specialties included management and policy-making problems, interactions outside the system, popularity of specialization, and process of admission to specialty programs. The necessity of need assessment, paying attention to the costs of healthcare interventions, defining the range of specialization, and revision of dental specialty programs are among the necessities of development of dental specialties. Conclusion: Dental specialties in Iran were developed at a time with inadequate attention to shortage of infrastructure based on political interactions. The popularity of specialization in dentistry and the associated high costs in a free educational system highlight the significance of need assessment regarding the number of specialists required in academic and therapeutic fields, and setting some criteria for development of specialty programs.